Inovasi Aplikasi Online Green Waqf Berbasis Blockchain Guna Pendanaan Produktivitas Tamanu Sebagai Upaya Pelestarian Lingkungan - Sukaina, Iin Dwi; Zahidah, Hana Fitria; Arifian, Falsa Dzaky (JIOSE: Journal of Indonesian Sharia Economics, 2022)
Various parties are required to innovate renewable energy to support life in the future. One of the innovations to support renewable energy is utilizing the tamanu plant (Calophyllum inophyllum). Tamanu plants can reduce carbon emissions and can be processed into cosmetic ingredients and medicines that have the potential to create a sustainable business. However, the development of industry requires large costs so adequate financing is needed. One of the financing models is green waqf in the form of money by utilizing blockchain. With blockchain storage technology, data can be maintained properly. Therefore, this research aims to describe an application innovation called "Tamanoo". This research data is secondary data with a qualitative descriptive approach and literature study. The mechanism involves waqif, mauquf alaih, and government. Tamanoo is a mobile application with an integrated system connecting wakif with the tamanu industry. Through crowdfunding, waqf funds can finance the sustainable Tamanu industry, including the plantation, pharmaceutical, and biofuel industries. The steps in implementing Tamanoo include designing to evaluate prototypes, raising funds, outreach to industrial and wakif activists, and commercialization and application implementation. Through Tamanoo, it will be easier for people to make endowments and contribute directly to economic recovery and environmental improvement.